2021
DOI: 10.1158/1078-0432.ccr-20-3471
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cell Chromosomal Instability and Neuroendocrine Phenotype by Immunomorphology and Poor Outcomes in Men with mCRPC Treated with Abiraterone or Enzalutamide

Abstract: Purpose: While the detection of AR-V7 in circulating tumor cells (CTC) is associated with resistance to abiraterone or enzalutamide in men with metastatic castration-resistant prostate cancer (mCRPC), it only accounts for a minority of this resistance. Neuroendocrine (NE) differentiation or chromosomal instability (CIN) may be additional mechanisms that mediate resistance. Experimental Design: PROPHECY was a multicenter prosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
1
19
0
1
Order By: Relevance
“…Further, CD56 was assessable in three NEPC patients (pts 10, 12, and 26) in which all had expression, and one CRPC-Adeno (pt 11) that did not have CD56 expression. Qualitatively, CTC morphologic features from NEPC were similar to previously described 10 , 14 . Of the detectable CTCs, 191 in total were isolated from the slide, and the genomic material was subjected to single-cell whole genome amplification and low-pass sequencing (Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Further, CD56 was assessable in three NEPC patients (pts 10, 12, and 26) in which all had expression, and one CRPC-Adeno (pt 11) that did not have CD56 expression. Qualitatively, CTC morphologic features from NEPC were similar to previously described 10 , 14 . Of the detectable CTCs, 191 in total were isolated from the slide, and the genomic material was subjected to single-cell whole genome amplification and low-pass sequencing (Fig.…”
Section: Resultssupporting
confidence: 79%
“…Qualitatively, several CTCs had characteristic features of small-cell NEPC-like morphology that included small-size, circular shape, high nuclear-to-cytoplasm ratio, and salt-and-pepper-like or textured chromatin observed by DAPI stain, akin to criteria used in a small-cell carcinoma diagnosis in tissues. These CTC criteria for NEPC were previously described in Beltran et al 10 and recently applied to a prospective cohort in Brown et al 14 . A DAPI texture mask is shown to illustrate the observed textured chromatin compared with a leukocyte for reference.…”
Section: Resultsmentioning
confidence: 99%
“…We present comprehensive analysis of CTC molecular profiles obtained in the context of a prospective clinical study of men with mCRPC treated with abiraterone or enzalutamide (PROPHECY), with the overall objective of developing a first-in-field CTC-based molecular taxonomy of ARSi resistance (Armstrong et al, 2019a). Prior studies from this cohort of patients have demonstrated the importance of AR-V7 detection in CTCs as well as CTC neuroendocrine phenotypes and a range of CTC DNA copy number alterations in abi/enza outcomes (Armstrong et al, 2020; Brown et al, 2021a; Gupta et al, 2021). However, the transcriptional mediators of AR therapy resistance or the immune signatures associated with outcomes were not described previously.…”
Section: Resultsmentioning
confidence: 90%
“…However, most studies have used ctDNA analyses to describe the genomic landscape of mCRPC focusing mostly on the AR gene and its treatment-associated genomic alterations (Annala et al, 2021; Romanel et al, 2015). In addition, our prior work has strongly associated the detection of AR-V7 in CTCs with AR therapy resistance, and CTC phenotypes and genotypes with these outcomes (Armstrong et al, 2019a; Brown et al, 2021a; Gupta et al, 2021). However, many DNA based alterations may lack a functional impact or phenotype, illustrating the need for broader phenotypic assays related to RNA expression both of tumor and immune cell subsets, which may better capture patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, CTC heterogeneity has been associated with poor prognosis in patients with CRPC treated with AR-targeted therapies (Scher et al 2017). In the multicenter PROPHECY study, CTCs were evaluated by the Epic platform in 107 men prior to receiving abiraterone or enzalutamide (Brown et al 2021). Of these, 8.7% had NEPC features defined by cell morphology and size, and their presence along with chromosomal instability in CTCs was associated with poor prognosis.…”
Section: :8mentioning
confidence: 99%